Batch and optimization studies of ciprofloxacin removal from aqueous solution by spent tea leaves - Lee, Shao Ken (2023)
The feasibility of spent tea leaves (STL) for the removal of ciprofloxacin (CIP) from aqueous solution was examined in this project. The effect of several experimental conditions was studied, including initial concentrations of adsorbate, adsorbent dosage, contact time, pH and agitation rate. Chemical modifications such as esterification and nitric acid modification were carried out to determine the influence on the adsorption performance. The equilibrium data of the adsorption of CIP by STL conform to both Langmuir and Brunauer-Emmett-Teller (BET) isotherm models, with R2 value of 0.9941. Furthermore, the experimental data fitted well into pseudo-second-order kinetic model with R2 values close to unity. The functional groups present on STL were determined using Fourier Transform Infrared Spectrophotometer (FTIR), and the surface morphology and topography were analyzed using Scanning Electron Microscope (SEM) and Atomic Force Microscope (AFM), respectively. Response Surface Methodology (RSM) was also employed in this work to determine the optimum conditions for the adsorption process. The optimum experimental conditions were found to be 40 mg/L of CIP concentration, 0.03 g of STL, pH 6.5, 150 rpm agitation rate and 182.5 minutes of contact time.